Great Plasticity in a Great Pathogen: Capsular Types, Virulence Factors and Biofilm Formation in ESBL-Producing Klebsiella pneumoniae from Pediatric Infections in Uruguay - Lucía Araújo; Romina Papa-Ezdra; Pablo Ávila; Victoria Iribarnegaray; Inés Bado; Hector Telechea; Virginia Garcia-Fulgueiras; Rafael Vignoli (Antibiotics, 2024)
Klebsiella pneumoniae is widely recognized as an opportunistic hospital and community pathogen. It is one of the priority microorganisms included in the ESKAPE group, and its antibiotic resistance related to extended-spectrum β-lactamases (ESBL) is a global public health concern. The multi-drug resistance (MDR) phenotype, in combination with pathogenicity factors, could enhance the ability of this pathogen to cause clinical infections. The aim of this study was to characterize pathogenicity factors and biofilm formation in ESBL-producing K. pneumoniae from pediatric clinical infections. Capsular types, virulence factors, and sequence types were characterized by PCR. Biofilm formation was determined by a semiquantitative microtiter technique. MDR phenotype and statistical analysis were performed. The K24 capsular type (27%), virulence factors related to iron uptake fyuA (35%) and kfuBC (27%), and sequence types ST14 (18%) and ST45 (18%) were the most frequently detected. Most of the strains were biofilm producers: weak (22%), moderate (22%), or strong (12%). In 62% of the strains, an MDR phenotype was detected. Strains with K24 capsular type showed an association with ST45 and the presence of fyuA; strains with kfuBC showed an association with moderate or strong biofilm production and belonging to ST14. Weak or no biofilm producers were associated with the absence of kfuBC. The MDR phenotype was associated with the main ESBL gene, blaCTX-M-15. The high plasticity of K. pneumoniae to acquire an MDR phenotype, in combination with the factors exposed in this report, could make it even more difficult to achieve a good clinical outcome with the available therapeutics.